The complete chloroplast genome sequence of Lotus corniculatus L. Issue 1 (2nd January 2021) - Jiang, Wenbo; Ma, Lin; Yi, Dengxia; Pang, Yongzhen
Abstract: Lotus corniculatus L., a member of the Fabaceae family, is considered one of the most agriculturally important forage plants, owing to its anti-bloating properties; its ability to grow in low-fertility, acidic, and high-salinity soils; and high nutritional value. In this study, we obtained the complete chloroplast genome of L. corniculatus by Illumina sequencing and GetOrganelle assembly pipeline. The whole chloroplast genome of L. corniculatus is 150, 700 bp in length, and has a typical circular structure with four parts: a large single-copy region (LSC 82, 117 bp), a small single-copy region (SSC 18, 275 bp), and a pair of inverted repeat regions (25, 154 bp for both IRa and IRb). The overall GC content is 36.03%. The plastome has 109 unique genes, consisting of 78 protein-coding genes, 27 unique tRNA gene, and 4 unique rRNA genes. Based on the protein-coding gene sequences from 17 species, we reconstructed a maximum likelihood (ML) tree. The phylogenetic result shows that L. corniculatus has a closer relationship with Lotus japonicas .